Didactic sequence for the study of the concepts of Mechanics using Arduino (Research, Society and Development, 2020)
This research presents a description and application of a didactic sequence, that involves basic mechanics concepts in the high school in the city of Acaraú-CE. Such didactic sequence is based on the proposal of Meaningful Learning, published by David Ausubel, according to which, learning becomes palpable to the student when he starts the prior knowledge with whom he wishes to learn, through teacher mediation. The methodology consists of using a practical experiment, to contextualize medium speed concepts, developed with support from the Arduino platform. The data were collected from the applied tests, developed activities and spontaneous or suggested reports from the students. The tests were applied in another class, in which the traditional methodology was used in order to compare performance. Thus, we propose here an alternative didactic sequence that, in addition to arousing the interest of students in the teaching of science, can favor the pedagogical action of the teacher.